‘Mental drought’ afflicts Uganda’s cattle corridor - Egeru, Anthony (ResearchGate, 2015)
Diagonally from south western to north eastern Uganda is an eco-region commonly referred to as the “cattle corridor”. It is Uganda’s semi-arid region. The region is synonymous with extreme climatic conditions, particularly drought and intermittent floods. However, drought has made this eco-region more of a resounding crisis region from time to time; partly because its peoples are pastoralists and agro-pastoralists highly dependent on rainfed production systems. Thus, in the event of a drought, livestock herders and farmers are often in crisis mode. How do we define drought? Drought can be considered as an extended period during which fresh water availability and accessibility is below normal, attributable to unfavourable distribution of rainfall, temperature, soil moisture and wind. There are different forms of drought, namely, meteorological drought, agricultural drought and hydrological drought.
Keywords: Mental drought; Uganda’s cattle corridor